Transformations of 'Sacredness in Stone': Religious Architecture in Urban Space in 21st Century Germany : New Perspectives in the Study of Religious Architecture - Wildt, Kim de (Religions, 2019)
Religious transformations in modern societies are not merely a discursive or demographic phenomenon, they also relate to religious architecture in urban space and affect the built environment at its core. Many churches, for instance, are in the process of reuse, closure, or even demolition. At the same time, there has been an increase in the construction of new mosques and a reorientation in synagogue architecture in Germany for the last twenty-five years. The three religious traditionsJudaism, Christianity, and Islamundergo remarkable transformations with regard to the design and style of their places of worship. Often, however, these new designs are not easily readable' to visitors and believers alike. In addition, the role of contemporary religious architecture in its relation to urban space is changing. Which meanings do religious buildings convey, how are they positioned, and how do they structure urban space? In collaboration of the study of religions and architectural history, we approach these questions by means of studying the transformations of contemporary religious architecture in Germany in a comparative manner. We survey Jewish, Christian, and Muslim places of worship, that is, new constructions, reused, and demolished buildings in Germany since 1990. The selected buildings are studied in detail regarding their meaning and positioning in urban space. This article presents findings from an ongoing research project and opens new perspectives in the study of urban religion.